Enhanced emission from mid-infrared AlInSb light-emitting diodes with p-type contact grid geometry - Meriggi, L.; Steer, M.; Ding, Y.; Thayne, I.; Macgregor, C.; Ironside, Charlie; Sorel, M. (American Institute of Physics Inc., 2015)
We report on the impact of lateral current spreading on light emission from aluminium indium antimonide (AlInSb) mid-infrared p-i-n light-emitting diodes (LEDs) grown by molecular beam epitaxy on a GaAs substrate. Due to the high effective mass of holes in AlxIn1-xSb, the resistivity of p-type material determines the 3-D distribution of current flow in the devices. This work shows that maximum light emission, as measured by electroluminescence, and 3-times wall-plug efficiency improvement were obtained at room temperature from devices with a p-type contact grid geometry with a spacing of twice the current spreading length in the p-type material, which was measured by spatially resolved photocurrent. The LED with the optimal contact geometry exhibits improved performance at high injection current levels thanks to the more uniform carrier distribution across the device area.